P36: SOMATIC SYMPTOM DISORDER (SSD) AND ABDOMINAL PAIN: INCREASED OPIOID PRESCRIBING IN SURGICAL PATIENTS. (27th April 2021) - Campbell, C; Stieler, M; Pockney, P; Shah, K; Thirugnanasundralingam, V; Spittal, M; Carter, G
Abstract: Introduction: Undifferentiated pain, and pain out of proportion of diagnosed pathology are sources of frustration to clinician and patient. SSD is a DSM-V diagnosis that has consolidated the previous diagnoses of psychogenic pain. It is a health anxiety condition, where sufferers experience multiple somatic symptoms which cause anxiety and distress. This anxiety results in frequent ED and GP presentations, extensive investigations, and increased opioid prescription. However, opioids do little to alleviate symptoms. Treatment should focus on underlying anxiety and depression. Population studies show SSD prevalence to be 15-20%, however SSD has never been studied in the surgical population. We hypothesized that the rates of SSD in the surgical population reflects that in primary care, and that SSD sufferers are more likely to be prescribed opioid analgesia. Method: Adult patients admitted with abdominal pain of any non-traumatic aetiology to the Acute General Surgical Unit at a major tertiary hospital are being screened for SSD using the PHQ-15 questionnaire, and opioid prescription is being recorded. Result: 400 participants have been recruited with a total SSD prevalence of 20%. Opioid prescribing rises sharply with SSD diagnosis. The average opioid prescription appears to be 3 times higher in patients with SSD compared to those without. Conclusion: Our data confirms an SSD prevalence of 20% in the surgical population. This is associated with increased opioid prescription. Early recognition of SSD and implementation of appropriate treatment could reduce hospital presentations, admissions and opioid prescription. We will continue recruitment to 800 participants by March 2020. Take-home message: SSD is common in all populations, and results in increased hospital presentations, admissions and opioid prescription. Early recognition and implementation of appropriate treatment may reduce healthcare burden, improve patient outcomes, and reduce opioid prescription.